Synthesis and processing of an Escherichia coli alkaline phosphatase precursor in vitro. - Inouye, H (1977)
Alkaline phosphatase [orthophosphoric-monoester phosphohydrolase (alkaline optimum), EC 3.1.3.1] of E. coli was synthesized in a cell-free system, and the size of the direct translation product was analyzed. The product has a higher molecular weight than the mature alkaline phosphatase found in the periplasm. The direct translation product can be processed to the mature size by an E. coli membrane fraction; the processing activity copurifies with the outer-membrane fraction. The presumed precursor can dimerize to form active enzyme without being processed, and the resultant enzyme appears to be more hydrophobic than the mature enzyme. These findings are discussed in connection with the "signal hypothesis" proposed for the excretion of proteins across membranes.